The assessment of occupational exposure of operation room personnel to isoflurane anesthetic gas - MJ Zare Sakhvidi; A Barkhordari; M Salehi; SH Behdad; MH Fallahzade (طب کار)
Background: The Operation room personnel are exposed to anesthestic gases such as Isoflurane. The Chronic exposure to such substances will increase the risk of abortion as well as congenital malformations. In this research, we have determined the amount of exposure to isoflurane gas in operation room air and the breathing zone of operation room personnel. Methods: An analytical cross sectional study was done on the concentration of isoflurane in far & near zones in ear, throat and nose operation room of a hospital with OSHA103 method using charcoal tube and analyzed by gas chromatography devices with flame ionization detector (GC/FID). Results: The average concentration of isoflurane gas was 4.059±4.073 mg/m3, Its maximum was19.597 mg/m3, its minimum was 0.122 mg/m3. The result showed that in 47.9% of the samples in near area, 33.3% in far area and 40.6% of the total samples, the amount of contamination in breathing zone of operation room personnel was higher than the allowed concentration as proposed in national institute of safety and health The results showed that there are not differences between the measured concentration in far & near areas. Conclusion: Contamination of isoflurane anesthetic gas is high in studied operating room. On the other hand the study showed that depending on the type of surgery, the generation rate of contamination in different days can be varied up to 17 times. So control measurement such as setting of air conditioning system and appropriate and standard cleaning in room and periodic monitoring of them is essential.